2020
DOI: 10.1186/s41687-020-00211-y
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome and oral health: mothers’ perception on their children’s oral health and its impact

Abstract: Background Individuals with Down syndrome exhibit particular oro-facial characteristics that may increase their risk of oral health problems. However, there is little research on the oral health of children and adults with Down syndrome and the way that oral health may affect Quality of Life (QoL). This study explored mothers’ perceptions of the oral health problems experienced by their children with Down syndrome and how these reported problems impacted the lives of the children and their families. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
(32 reference statements)
0
26
0
1
Order By: Relevance
“…Al Bandary H. Al Jameel et al . [ 24 ] conducted a study to examine the perceptions of mother on the oral health issues experienced by their children with Down syndrome. It was concluded that the predominant oral health–related problem reported by mothers was difficulty in speaking.…”
Section: Discussionmentioning
confidence: 99%
“…Al Bandary H. Al Jameel et al . [ 24 ] conducted a study to examine the perceptions of mother on the oral health issues experienced by their children with Down syndrome. It was concluded that the predominant oral health–related problem reported by mothers was difficulty in speaking.…”
Section: Discussionmentioning
confidence: 99%
“…Também possuem uma maior predisposição a distúrbios orofaciais tais como doença periodontal, má oclusão, distúrbios dos tecidos moles, incluindo protrusão da língua ou lábios invertidos. Os sintomas orais como dor, desconforto ou dificuldade de mastigar, e os problemas sistêmicos, nutritivos e digestivos podem causar grande impacto na vida desses indivíduos, estendendo-se a efeitos maiores na qualidade de vida, entre eles sociais e emocionais (Aljameel et al, 2020).…”
Section: Contextualização Da Síndrome De Down Na Odontologiaunclassified
“…4 Children with DS tend to have poor oral hygiene as they are unable to understand and are unaware of the importance of oral hygiene. 5 Oral hygiene problems commonly found in children with DS are gingivitis, periodontal problems, pain, infection, and problems with the masticatory system. 6 Mental retardation or MR, developmental delay, physical disability, and other problems could affect disabled children's daily activities and are reasons why they could not maintain their oral hygiene.…”
Section: Introductionmentioning
confidence: 99%